Maximal inequality along curves associated with oscillatory integral operator - Yaoming Niu; Ying Xue (Journal of Inequalities and Applications)
Abstract In this paper, we establish maximal estimates along curves for a class of multiparameter oscillatory integral operators, which can be seen as an extension to the results of the Schrödinger type multiparameter operators of Sjolin and Soria (J. Math. Anal. Appl. 411:129–143, 2014) and Cho, Lee, and Vargas (J. Fourier Anal. Appl. 18:972–994, 2012) to Schrödinger operators along the curves.